A explicação da obesidade a partir dos traços de personalidade e hábitos alimentares - Oliveira, Jessica Queiroga de (2017)
This dissertation aimed to explain obesity from personality traits, eating habits, quality of life, anxiety and depression. In this sense, two empirical studies were carried out. Study 1 aimed to validate for the local context the Eating Habits Scale, originally Portuguese and the Hospital Anxiety and Depression Scale. A total of 335 people aged 17-48 years (M = 23.2, SD = 5.9) participated in the study, of whom 80.7% were 26 years old. The subjects were predominantly female and single, accounting for 57.8% and 79% of the sample, respectively. They answered a questionnaire composed by the Eating Habits Scale, Anxiety and Depression Scale and a sociodemographic questionnaire. The results suggested reducing the Eating Habits Scale, with its final version with 25 items, as well as the Anxiety and Depression Scale, containing 13 items in its final version. Study 2 proposed an explanatory model for obesity, considering the traits of personality, eating habits, quality of life, anxiety and depression. The sample plan used was stratified sampling by allocation, thus, 329 individuals, aged between 17 and 59 years (M = 23 years, SD = 5.61), with a small majority of men (50.5%), Predominantly single (78.7%). The decision model was not fully adequate through the use of the multinomial logistic regression model, however, important variables were identified as predictors of some categories of Body Mass Index (BMI) classification. Among these, we can mention: depression and the personality trait conscientiousness for obesity grade 1 and the personality trait of opening to the change for low weight. The results were generally satisfactory. The instruments can be used to evaluate the Eating Habits, Anxiety and Depression, as well as obesity. Obesity prevention strategies can be operationalized from the results found.